Triggers and obstacles to the development of the FinTech sector in Poland - Agata Kliber; Barbara Będowska-Sójka; Aleksandra Rutkowska; Katarzyna Świerczyńska (Risks, 2021)
The article aims to show the opportunities for the formation of new FinTech startups in Poland and further development of the sector, as well as to identify the most critical threats. The study offers the descriptive and deductive analysis based on the literature review. The empirical part relies on the data from external databases as well as the dataset collected in a survey run among the FinTechs in Poland in January 2020. The paper reveals that Poland is a fast-growing FinTech market which satisfies various requirements such as the number of secure Internet servers, mobile telephone subscriptions, the available labor force, as well as growing tertiary education enrolment. The crucial obstacles to the development of the sector is the uncertainty about the availability of skilled workers in the future and the lack of proper legal regulations.
Keywords: 330; development; economic environment; FinTech